Bibliometric analysis of teen pregnancy research in Asia-Africa: Explore the future scope - Esti Nugraheny; Bunga A Paramashanti; Eny R Ambarwati; Yanti Yanti; Ocktariyana Ocktariyana; Tri Sunarsih; Zulvi Wiyanti; Hadi Ashar (Journal of Education and Health Promotion)
BACKGROUND: Adolescent pregnancy is prevalent in Asian-African countries. Hence, it is critical to track the progress of research and development trends related to the topic. The study aimed to characterize published articles on teen pregnancy by measuring the authors’ country and affiliation, most relevant and cited journals, thematic research, and growth trends. MATERIALS AND METHODS: Descriptive statistics and retrospective bibliometric analysis were used. Using the Scopus database, we collected published articles from 2010 to 2023. Titles and abstracts were screened. Eligible papers were reviewed based on co-occurrence analysis. Classification and visualization of results were conducted using VOSviewer software version 1.6.17. RESULTS: A total of 369 articles were relevant and included in the review. The countries that produced the most publications were South Africa and the United States. The most relevant affiliation was with the University of Cape Town, the University of the Witwatersrand, and the University of Kwazulu-Natal. The most relevant source journals were PLOS One, Reproductive Health, and BMC Public Health. The most cited sources were Lancet, PLOS One, and AIDS Journal. Four clusters were obtained that reflect the main topics, including human immunodeficiency virus (HIV) infection, child, health services, and pregnancy. The current research terms include HIV infection and maternal health services. CONCLUSIONS: This study suggests more research on the term “vertical transmission, breastfeeding, and partner violence” related to teen pregnancy. In addition, this research will inspire researchers and adolescent health policymakers to expand the scope of research to solve teenage pregnancy problems based on interdisciplinary theories and methods.